(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2003)
Argyropelecus logearti Arambourg, 1929 is redescribed in detail based on new material. The material consists of many unreported specimens from type and other localities. Based on new information presented here Argyropelecus logearti is interpreted to be most closely related to the extant species Argyropelecus hemigymnus. Argyropelecus logearti provides an early fossil that can be placed in the phylogenetic context of living Argyropelecus species. Argyropelecus has a fossil record ranging from Oligocene to Pleistocene. Fossil representatives of this genus are listed here for future reference.